2010
DOI: 10.1128/cvi.00368-09
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic Definition of Effector and Memory T-Lymphocyte Subsets in Mice Chronically Infected withMycobacterium tuberculosis

Abstract: The bacterium Mycobacterium tuberculosis remains one of the world's most successful pathogens, a situation that is aggravated by the fact that the existing vaccine, Mycobacterium bovis BCG, is not effective in adults. As with any vaccine, the purpose of giving BCG vaccination is to establish a long-lived state of memory immunity, but whether this is successfully completely established is still unclear. It is generally accepted that memory T cells can be divided into central and effector memory populations by f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
108
2
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(117 citation statements)
references
References 43 publications
6
108
2
1
Order By: Relevance
“…It has previously been shown that in mice vaccinated with BCG, the T cells are primarily effector or effector-memory T cells 6 mo after vaccination (32). In contrast we have shown that 1 y after vaccination with a fusion protein (H1) formulated in the same adjuvant used in this study, the T cells are primarily central memory T cells (33).…”
Section: Discussioncontrasting
confidence: 47%
“…It has previously been shown that in mice vaccinated with BCG, the T cells are primarily effector or effector-memory T cells 6 mo after vaccination (32). In contrast we have shown that 1 y after vaccination with a fusion protein (H1) formulated in the same adjuvant used in this study, the T cells are primarily central memory T cells (33).…”
Section: Discussioncontrasting
confidence: 47%
“…Meta-analysis of 14 prospective and 12 case-control studies revealed that the protective efficacy of BCG against pulmonary disease varies significantly with geographical latitude (14). This vaccine also appears to generate CD4+ central memory T cells rather poorly, potentially compromising control of subsequent TB infection (19,20). Another factor that may underlie BCG failure is the unusually high concentrations of IL-4 that have been found in patients from developing countries (21,22).…”
Section: Resultsmentioning
confidence: 99%
“…It has previously been reported that BCG is unable to maintain a large population of high-quality memory cells (10,36,54). BCG-promoted responses are (like the real TB infection) dominated by effector-like T cell subsets secreting IFN-g and/or TNF-a (41,54,55), and the numbers of IL-2 + T cells are much lower than after a H1/CAF01 subunit vaccination (36). The recent identification of BCG-specific CD4 T cells with a central memory phenotype (based on CCR7 expression) in a longitudinal study of infants (29) seems at odds with the observations in the mouse model and led Soares et al (29) to suggest that BCG might be cleared more rapidly in humans than in mice.…”
Section: Discussionmentioning
confidence: 99%